Immunohistochemical Expression of Human Epidermal Growth Factor Receptor 2 and Ki67 in Apocrine Gland Anal Sac Adenocarcinoma - Paiva, Felipe [UNESP]; Santos, Júlio; Carra, Gabriel [UNESP]; Sueiro, Felipe; Jark, Paulo; Nardi, Andrigo [UNESP] (MDPI, 2024)
Apocrine gland anal sac adenocarcinoma is an aggressive neoplasm, and surgery remains the treatment of choice, although it is controversial in advanced cases. The prognostic factors are not well established. Human Epidermal Growth Factor Receptor 2 (HER2) is a membrane protein related to tumorigenesis, whereas Ki67 is a nuclear protein related to cell proliferation. Both are potential prognostic markers and therapeutic targets. This study aimed to evaluate the expression of HER2 and Ki67 markers in canine apocrine gland anal sac adenocarcinoma. The tumor samples were divided into four groups: largest tumor diameter less than 2.5 cm, largest tumor diameter greater than 2.5 cm, metastatic lymph nodes, and control group of non-neoplastic anal sacs. Each contained 10 samples. Immunohistochemistry was performed to verify the expression of HER2 and Ki67 markers. Positive HER2 staining was observed in 45% of the neoplastic cases and negative HER2 staining in 100% of the control group. The Ki67 expression had a median of 25% in all groups, except for the control group, which had a median of 8%. The HER2 and Ki67 expression was present in apocrine gland anal sac adenocarcinoma, making them potential therapeutic targets. However, it was not possible to determine the clinical value of either marker.
Keywords: anal sac apocrine adenocarcinoma; immunohistochemistry; neoplasia; prognosis; therapeutic target